PENGARUH ROTASI KERJA TERHADAP KINERJA PEGAWAI DI LEMBAGA PEMASYARAKATAN NARKOTIKA KELAS IIA YOGYAKARTA - Annisa Primaharani; Kusmiyanti (Jurnal Komunikasi Hukum, 2024)
This research aims to analyze the effect of job rotation on employee performance at the Class IIA Narcotics Prison in Yogyakarta. Job rotation is considered an important strategy in the development of employee knowledge and skills, with the aim of improving work effectiveness and efficiency. The research method used is quantitative with a survey approach involving all employees of Class IIA Yogyakarta Prison as respondents. Data were obtained through questionnaires and analyzed using Smart-PLS. The research results show that job rotation has a positive and significant effect on employee performance. Employees who participate in job rotation experience an increase in skills, flexibility, and adaptability. Age and length of service factors influence employees' perceptions of job rotation, where younger employees are more likely to see rotation as an opportunity, while more senior employees view it as a challenge. This research concludes that well-planned job rotation can improve the quality and productivity of employee performance.